2023
DOI: 10.1177/11786388231190515
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity, Nutritional Status, and Associated Factors Among Pregnant Women in Their First Trimester of Pregnancy in Ambo District, Western Ethiopia

Mitsiwat Abebe Gebremichael,
Tefera Belachew Lema

Abstract: Background: Poor dietary diversity and undernutrition is a major public health concern for pregnant mothers. Optimal dietary diversity is essential during pregnancy since nutritional deficiencies may have a significant impact on both the mother’s and the fetus’s health. Pregnant women in Ambo district had inadequate dietary diversity and were undernourished, but their status during the first trimester of pregnancy was not known. As a result, the objective of this research was to assess the dietary diversity, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…On the other hand, the finding of the present study is comparable to that of Solomon et al [ 24 ] and Sekartaji et al [ 34 ], who reported rates of 59.6% and 63.2% respectively. This variation in results may partly be attributed to differences in methodologies [ 35 , 36 ], population characteristics [ 35 ], nutrition knowledge of mothers [ 37 ], economic conditions [ 38 ], women`s empowerment and food security [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the finding of the present study is comparable to that of Solomon et al [ 24 ] and Sekartaji et al [ 34 ], who reported rates of 59.6% and 63.2% respectively. This variation in results may partly be attributed to differences in methodologies [ 35 , 36 ], population characteristics [ 35 ], nutrition knowledge of mothers [ 37 ], economic conditions [ 38 ], women`s empowerment and food security [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, Sema et al [ 49 ], in a study that determined the MDD and related factors among children aged 6–23 months, failed to show a correlation between MDD and child’s gender, maternal educational status and number of ANC visits by mothers. The mixed findings could, at least in part, be attributed to the methodological variances among the studies [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%